Acute Exertion Elicits a H2O2-Dependent Vasodilator Mechanism in the Microvasculature of Exercise-Trained but Not Sedentary Adults. Issue 1 (January 2015) - Durand, Matthew J.; Dharmashankar, Kodlipet; Bian, Jing-Tan; Das, Emon; Vidovich, Mladen; Gutterman, David D.; Phillips, Shane A.
<x xml:space="preserve">Abstract</x> Brachial artery flow–mediated vasodilation in exercise-trained (ET) individuals is maintained after a single bout of heavy resistance exercise compared with sedentary individuals. The purpose of this study was to determine whether vasodilation is also maintained in the microcirculation of ET individuals. A total of 51 sedentary and ET individuals underwent gluteal subcutaneous fat biopsy before and after performing a single bout of leg press exercise. Adipose arterioles were cannulated in an organ bath, and vasodilation to acetylcholine was assessed±the endothelial nitric oxide inhibitorL-NG-nitroarginine methyl ester, the cyclooxygenase inhibitor indomethacin, or the hydrogen peroxide scavenger polyethylene glycol catalase. Separate vessels (isolated from the same groups) were exposed to an intraluminal pressure of 150 mm Hg for 30 minutes to mimic the pressor response, which occurs with isometric exercise. Vasodilation to acetylcholine was reduced in microvessels from sedentary subjects after either a single weight lifting session or exposure to increased intraluminal pressure, whereas microvessels from ET individuals maintained acetylcholine-mediated vasodilation. Before weight lifting, vasodilation of microvessels from ET individuals was reduced in the presence of L-NG-nitroarginine methyl ester and indomethacin. After weight lifting or exposure to increased intraluminal pressure, polyethylene glycol catalase significantly reduced vasodilation, whereas L-NG-nitroarginine methyl ester and indomethacin had no effect. These results indicate that (1) endothelium-dependent vasodilation in the microvasculature is maintained after heavy resistance exercise in ET individuals but not in sedentary subjects and that (2) high pressure alone or during weight lifting may induce a mechanistic switch in the microvasculature to favor hydrogen peroxide as the vasoactive mediator of dilation.